20 Myths about Religion and Politics in America - Burge, Ryan P. (Book collections on Project MUSE., 2022)
The way most people think about religion and politics is only loosely linked to empirical reality, argues Ryan P. Burge. In 20 Myths about Religion and Politics in America, Burge strives to be an impartial referee and to overcome these caustic misperceptions by using both rigorous data analysis and straightforward explanations.